Barriers and facilitators to health screening in men: A systematic review. (September 2016) - Teo, Chin Hai; Ng, Chirk Jenn; Booth, Andrew; White, Alan
Abstract: Rationale: Men have poorer health status and are less likely to attend health screening compared to women. Objective: This systematic review presents current evidence on the barriers and facilitators to engaging men in health screening. Methods: We included qualitative, quantitative and mixed-method studies identified through five electronic databases, contact with experts and reference mining. Two researchers selected and appraised the studies independently. Data extraction and synthesis were conducted using the 'best fit' framework synthesis method. Results: 53 qualitative, 44 quantitative and 6 mixed-method studies were included. Factors influencing health screening uptake in men can be categorized into five domains: individual, social, health system, healthcare professional and screening procedure. The most commonly reported barriers are fear of getting the disease and low risk perception; for facilitators, they are perceived risk and benefits of screening. Male-dominant barriers include heterosexual -self-presentation, avoidance of femininity and lack of time. The partner's role is the most common male-dominant facilitator to screening. Conclusions: This systematic review provides a comprehensive overview of barriers and facilitators to health screening in men including the male-dominant factors. The findings are particularly useful for clinicians, researchers and policy makers who are developing interventions and policies to increase screening uptake in men. Highlights: Health screening uptake in men is influenced by widely varying factors. Commonly reported barriers include fear of getting the disease and low risk perception. Commonly reported facilitators include perceived at risk and benefits of screening. Male-dominant barriers include heterosexual self-presentation and to avoid femininity. Partner's role is the most commonly reported male-dominant facilitator to screening.